Aspectos léxico-semánticos de los verbos prestados del inglés - Salamon, Marta (Studia Romanica Posnaniensia, 2004)
The purpose of the present article is to analyse the most important lexical and semantic aspects of the verbs borrowed from English that appear in the contemporary Spanish. The main emphasis is put on the morphological adaptation of the words of English origin and its influence on their semantic transparency. Furthermore, the article presents a diffusion of these loanwords into different registers of Spanish, paying special attention to their role in the technical vocabulary, as well as their usage in the jargon of Spanish teenagers.